Pengaruh Green Accounting, Corporate Social Responsibility, dan Kinerja Keuangan terhadap Nilai Perusahaan - Dina Dwi Rahmawati; Hari Setiono; Muhammad Bahril Ilmiddaviq (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
In protecting the environment, companies have an important role, such as carrying out green accounting and corporate social responsibility. Implementing these two responsibilities will have an impact on financial performance and profitability, which can increase company value. This research aims to determine the influence of green accounting, corporate social responsibility, and financial performance on company value. The object of this research is to compare manufacturing companies with the food and beverage company sub-sector listed on the Indonesia Stock Exchange for the 2019–2022 period. We obtained the data from manufacturing company financial reports published on the IDX and the company's official website. Data analysis was carried out using the SEM Partial Least Square (PLS) method using SmartPLS version 3 software. The results of this research show that green accounting, corporate social responsibility, and financial performance have no effect on company value, while profitability has an effect on company value.